Strategi Pemasaran Produk Tabungan iB Muamalat Haji pada PT Bank Muamalat Indonesia KCP Rantauprapat - Muhammad Ravi Akbar; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to determine the marketing strategy of the iB Muamalat Haji Savings product at Bank Muamalat KCP Rantauprapat. This research is a type of descriptive research using a qualitative approach. Information obtained from the results of interviews, literature review sourced from journals and critical thinking from the author. Based on the results of the author's research at PT Bank Muamalat KCP Rantauprapat. So what can be concluded from the company where the author carries out practical internship work, namely as follows; Bank Muamalat is one of the first Islamic banks established in Indonesia in 1991, which focuses on financing Hajj savings and other large projects. Just like Banks in general, they can also make Deposits, Current Accounts and Savings; PT Bank Muamalat KCP Rantauprapat is a bank that operates based on sharia principles in accordance with the regulations set by the government. This is reinforced by every transaction with customers using contracts such as Mudharabah, Murabahah, Musyarakah, Ijarah.